Catalytic co-pyrolysis of palm oil biomass and surgical face mask waste for bio-oil production - Wee, Melvin Xin Jie (Curtin University, 2023)
This project explores the conversion of waste materials, specifically empty fruit bunches (EFB) and disposable surgical face masks (SFM), via co-pyrolysis. A maximum pyrolytic oil yield of 19.49 wt.% with a 15 wt.% HZSM-5 catalyst at a 1:1 feedstock ratio and 500 °C was achieved. Additionally, the development of an artificial neural network (ANN), the thermo-kinetic parameters, and the reaction pathway of catalytic co-pyrolysis were also investigated.